(untitled) (Bangladesh Journal of Radiology and Imaging, 2026)
Background: Breast cancer (BC) is one the most common malignancies among women in Bangladesh, contributing significantly to morbidity and mortality within this low- and middle-income country (LMIC) context. Epidemiological evidence suggests that BC onset in South Asia occurs at a considerably younger age than in Western populations, necessitating localized age-specific data for effective public health policy. Methods: This retrospective, hospital-registry based study analyzed histopathologically confirmed female BC cases presenting at three major tertiary care facilities in Dhaka, Bangladesh. Descriptive statistics, including Mean, Median, Mode, and Standard Deviation, were calculated, and cases were grouped into 5-year age intervals to determine age-specific incidence patterns. Results: A total of N=3117 histopathologically confirmed female breast cancer cases were included in this analysis, representing a wide age range of presentation across three major tertiary care facilities. Breast cancer cases among women aged 30–34 constituted approximately 4% of diagnoses, while incidence doubled to 8.3% in the 35–40 age group. This sharp increase occurred five years earlier than peaks observed in Western populations, where incidence typically rises after 40. The trend aligns with reports from other South and East Asian countries showing an earlier onset and higher rates of triple-negative and aggressive subtypes. Conclusion: Initiating breast cancer screening at age 35 is evidence-based and contextually appropriate for Bangladesh. Earlier screening could improve detection of treatable disease, reduce late-stage presentation, and align national strategies with the region’s distinct epidemiological profile. This shift is a practical approach to strengthen cancer control in resourcelimited settings.